Suicídio de idosos e mídia: o que dizem as notícias? - PEREIRA, Beltrina da Purificação da Côrte (2016)
How is the media addressing elderly suicide? And what does the news about elderly suicide tell us? These were the questions which guided this reflection, addressing the news about elderly suicide published on Brazilian media from April 2010 to April 2013. We have noticed that the word ¨suicide” – that until recently “should not be mentioned” by the media – appears in most of the news, both in its headlines and inside the texts, showing that suicide, as a public health issue, moves from the private field to occupy and compose the public space. We found out that the main risk situations that lead seniors to commit an extreme communication gesture resulted from the effects of recessive economic politics, as well as life extension without dignity in view of the fear of dependence and causing trouble to other people. Such situations indicate the need of developing and strengthening social support networks.